Physicochemical Analysis And Storage Stability Of Unpasteurised And Pasteurised Juice Powder From Sweet Potato (Ipomoea Batatas L.) Haulm - Nurhani Fatihah Binti Mohd Hanifah (Universiti Sains Islam Malaysia, 2024)
Matric:3201437(FST)